Advanced heat transfer fluids for direct molten salt line-focusing CSP plants. (July 2018) - Bonk, Alexander; Sau, Salvatore; Uranga, Nerea; Hernaiz, Marta; Bauer, Thomas
Abstract: Concentrating solar power coupled to thermal energy storage (TES) is a vastly growing industrial process allowing for the generation of dispatchable and green electricity. This paper focuses on direct molten salt line-focusing technology using linear Fresnel and parabolic trough collector systems. Direct molten salt technology utilizes molten salt as heat transfer fluid in solar field and TES medium. Nitrate salts can be applied since they cover a wide temperature range. As storage medium Solar Salt, a binary NaNO 3 − KNO 3 (60–40 wt%) mixture, is most commonly used but variations of this system have promising thermal properties in terms of a lower melting temperature to minimize the risk of undesired salt freezing events. These modified salts are typically ternary, ternary reciprocal or higher order systems formed by adding additional cations, anions or both. In this study five molten salt systems Solar Salt, HitecXL (CaKNa//NO3), LiNaK-Nitrate, Hitec (NaK//NO23) and CaLiNaK//NO23 are both investigated and critically reviewed. Their thermo-physical properties including phase diagrams, composition, melting ranges, melting temperature, minimum operation temperature, thermal stability, maximum operation temperature, density, heat capacity, thermal conductivity, viscosity and handling are evaluated and the most recommended values are discussed and highlighted. This review contributes to a better understanding of how the listed properties can be determined in terms of measurement conditions and provides temperature dependent data useful for future simulations of direct molten salt LF CSP plants.